PENGARUH CITRA MEREK, FASILITAS, DAN KUALITAS PELAYANAN TERHADAP KEPUASAN DAN LOYALITAS PASIEN RAWAT JALAN UNTUK MEMANFAATKAN PELAYANAN KESEHATAN DI RUMAH SAKIT SEMEN GRESIK - Nur Jannah (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2017)
This research has a goal to analyze the influence parcially and concurrently between brand image, facility, and service's quality for satisfaction and loyalty; and the influence of brand image, facility and service's quality to layalty by satisfaction. The sample of this research was used 100 respondents who are outpatients that exploit the health's service of Semen Gresik Hospital (havi ng minimal two times visit and 17years old). The methode of this analysis is Path Analysis. The result showed that brand image is not influential parcially for satisfaction; facility is not influential parcially for patient's satisfaction; service's quality is not influential parcially for satisfaction; brand image, facility and service's quality are influenced concurrently for satisfaction; brand image is not influential parcially for loyalty; facility is not influential parcially for loyalty; service's quality is influenced parcially for loyalty; satisfaction is influenced parcially for loyalty; brand image, facility, service quality and satisfaction are influenced concurrently for loyalti; brand image is influenced for loyalty by satisfaction, facility is influenced for loyalty by satisfaction and service quality is influenced for loyalty by satisfaction.